2021
DOI: 10.1088/1361-6528/ac378a
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial selectivity with an array of phthalocyanines functionalized TiO2/ZnO heterojunction thin film sensors

Abstract: The development of electronic noses requires the control of the selectivity pattern of each sensor of the array. Organic chemistry offers a manifold of possibilities to this regard but in many cases the chemical sensitivity is not matched with the response of electronic sensor. The combination of organic and inorganic materials is an approach to transfer the chemical sensitivities of the sensor to the measurable electronic signals. In this paper, this approach is demonstrated with a hybrid material made of pht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…All of the measurements were performed at room temperature (25 °C). In our case, the sensor response (relative resistance change) was measured from the following equation R = { R false( normala normali normalr false) R false( normalg normala normals false) R false( normalg normala normals false) = Δ R R } where R (air) and R (gas) are the resistances of the sensor before and after gas exposure, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All of the measurements were performed at room temperature (25 °C). In our case, the sensor response (relative resistance change) was measured from the following equation R = { R false( normala normali normalr false) R false( normalg normala normals false) R false( normalg normala normals false) = Δ R R } where R (air) and R (gas) are the resistances of the sensor before and after gas exposure, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The functionalized thin film showed a higher selectivity and sensitivity toward TEA detection, which is the major VOC exhaled through breath in patients with liver diseases. 30 On the other hand, Reji and the group reported VOC adsorption studies on the metal-free as well as Fe(II)phthalocyanine, which showed J-aggregation in the solid state. Contrary to the metal-free phthalocyanine, Fe(II)phthalocyanine exhibits a selective photoresponse to nonanal and 1-hexanol under dark and illumination of visible light, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sivalingam and co-workers showed how gas adsorption affects the surface PVT of a phthalocyanine-coated TiO 2 thin film as a biomarker for liver disorders. The functionalized thin film showed a higher selectivity and sensitivity toward TEA detection, which is the major VOC exhaled through breath in patients with liver diseases . On the other hand, Reji and the group reported VOC adsorption studies on the metal-free as well as Fe­(II)­phthalocyanine, which showed J -aggregation in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, TiO 2 generally demonstrates lower response towards majority of gases and has lower electrical conductance than more commonly used metal oxides – SnO 2 , ZnO, WO 3 , In 2 O 3 etc., which makes it less convenient for practical applications. However, TiO 2 attracts attention due to high selectivity of response, caused by the formation of anatase/rutile homojunctions and heterojunctions with other semiconductor oxides [8–11] . Doping with Nb(V) has been widely exploited for the improvement of electrical, optical and sensor characteristics of TiO 2 [12–18] .…”
Section: Introductionmentioning
confidence: 99%
“…However, TiO 2 attracts attention due to high selectivity of response, caused by the formation of anatase/rutile homojunctions and heterojunctions with other semiconductor oxides. [8][9][10][11] Doping with Nb(V) has been widely exploited for the improvement of electrical, optical and sensor characteristics of TiO 2 . [12][13][14][15][16][17][18] It has been reported that Nb(V) doping also provides a stabilizing effect by suppressing the temperature induced anatase to rutile phase transformation, leading to a decrease in sensor sensitivity.…”
Section: Introductionmentioning
confidence: 99%